Effects of extra training with active cycle of breathing technique relative to whole-body breathing exercise in older adults with stable COPD - Huiping Lai; Lanzhen Chen; Roger W. Chan; Qiongrong Pan; Qing Chen; Ying Chen; Zhenyu Xie (PLoS ONE, 2026)
Objective To examine the effects of extra training with active cycle of breathing technique (ACBT) as compared to whole-body breathing exercise (WBBE) in older adults with stable chronic obstructive pulmonary disease (COPD). Methods Fifty-one participants with stable COPD were randomly assigned into experimental group undergoing extra training of ACBT plus WBBE ( n = 25), and control group undergoing WBBE only ( n = 26), 30 minutes daily for 3 months. Lung function including forced expiratory volume in one second (FEV1), FEV1 in percentage of predicted value (FEV1%) and FEV1/forced vital capacity (FVC) ratio; exercise capacity (six-minute walk test distance, 6MWD); dyspnea symptoms (modified Medical Research Council, mMRC dyspnea scale score and Dyspnoea-12-Chinese/D-12-C scale score); and quality of life in terms of COPD Assessment Test (CAT) score before and after intervention were evaluated. Results Significantly higher FEV1 (1.82L versus 1.76L, p < 0.05) was found for the experimental group, with no significant differences in FEV1% and FEV1/FVC ratio. Significantly larger 6MWD (359.72m versus 340.18m, p < 0.001), significantly lower D-12-C scores (11.47 versus 13.55, p < 0.001), and significantly lower CAT scores (2.95 versus 3.98, p < 0.001) were observed in the experimental group relative to the control group. Conclusions Our findings suggested that ACBT in conjunction with WBBE could be effective complementary approaches for improving lung function and exercise capacity, reducing dyspnea symptoms, and enhancing quality of life in older adults with stable COPD. Future studies may explore how ACBT and WBBE could be optimized in training frequency, intensity, and duration specifically for older adults.